The effect of weight training and plyometric to develop muscular ability in the triple jump event for young people (Journal of the College of Basic Education, 2024)
The research aims to identify:1- Preparing training units using weights and plyometrics to develop muscular ability in the triple jump event for young people that are compatible with the capabilities of the research sample.2- Identify the effect of training units using weights and plyometrics in developing muscular ability in the triple jump event for young people.The experimental approach was used, and 4 players aged 18-19 years old were selected from the specialized school for track and field events.The results showed a positive effect between the pre- and post-tests of the experimental group and in favor of the post-tests on the dependent variables under study.It has been recommended to train trainers to use modern methods during the training process, such as using weight training and plyometrics, because the trainer’s knowledge of the training method makes it easier for him to train with it.